2021
DOI: 10.48550/arxiv.2111.05836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnetic fields in star formation: a complete compilation of all the DCF estimations

Junhao Liu,
Keping Qiu,
Qizhou Zhang

Abstract: The Davis-Chandrasekhar-Fermi (DCF) method provides an indirect way to estimate the magnetic field strength from statistics of magnetic field orientations. We compile all the previous DCF estimations from polarized dust emission observations and re-calculate the magnetic field strength of the selected samples with the new DCF correction factors in Liu et al. (2021). We find the magnetic field scales with the volume density as B ∝ n 0.57 . However, the estimated power-law index of the observed B − n relation ha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Therefore, one should clearly state the magnetisation level of turbulence (sub-or super-Alfvénic) before arguing about the relative contribution of the various terms in the energy balance. Liu et al (2021) further argues that self-gravity may modify this energy balance. We do not include gravity in this study, but it is possible that gravity may collapse locally bound (by self-gravity) regions in the ISM, enhancing and creating strong magnetic fields (Sur et al 2010).…”
Section: Discussion Of Section 4 and Caveatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one should clearly state the magnetisation level of turbulence (sub-or super-Alfvénic) before arguing about the relative contribution of the various terms in the energy balance. Liu et al (2021) further argues that self-gravity may modify this energy balance. We do not include gravity in this study, but it is possible that gravity may collapse locally bound (by self-gravity) regions in the ISM, enhancing and creating strong magnetic fields (Sur et al 2010).…”
Section: Discussion Of Section 4 and Caveatsmentioning
confidence: 99%
“…If we interpret this experiment at face value, this means that if individual clouds are sub-Alfvénic, we should expect correlated turbulent velocities beyond the extent of the entire sub-Alfvénic region, even if the driving scale is not itself larger than the individual clouds. For the ISM in general, which is probably trans-Alfvénic-to-super-Alfvénic and trans-sonic on average (Gaensler et al 2011;Krumholz et al 2020;Liu et al 2021;Seta & Federrath 2021b), we should expect turbulent motions to be correlated out to the driving scale of the largest turbulent motions. This, of course, is a natural repercussion of one of the central tenets of turbulence: the energy cascade from large (galactic, in this context) to small (molecular cloud and smaller, Armstrong et al 1995) scales.…”
Section: The Averaging Scalementioning
confidence: 99%
“…We see some suggestion that isolated cores have lower field strengths for a given density than do structures under stellar feedback, suggesting that B 0 , n 0 and κ may vary with environment. Liu et al (2021b) found a best-fit power law for their compilation of DCF results of κ = 0.57 ± 0.03, between the weak-and strong-field values.…”
Section: Magnetic Field Strength -Density Relationshipmentioning
confidence: 96%
“…As the analysis which we can perform in this chapter is very limited, we have made this data set available as a resource 6 . We draw attention to a recent analysis of a compilation of emission DCF measurements by Liu et al (2021b).…”
Section: Compilation Of Literature Dcf Field Strengthsmentioning
confidence: 99%
“…On these scales, the field is tangled, chaotic (at least for M A 2, , and different regions in space have causally disconnected magnetic fields. For average ISM parameters, M A ≈ 2 (Gaensler et al, 2011;Krumholz et al, 2020;Liu et al, 2021;, 0 ∼ 100 pc (∼ the Galactic disk scale-height; Karlsson et al, 2013;Falceta-Gonc ¸alves et al, 2014;Li et al, 2014;Krumholz and Ting, 2018), then on scales beyond cor ∼ 25 pc streaming cosmic rays, locked to magnetic field lines, take tangled, chaotic paths that resemble a random walk, leading to a spatial dispersion between cosmic rays originating from the same source. We call this process the "macroscopic diffusion" of SCRs.…”
Section: Cosmic Rays and The Streaming Instabilitymentioning
confidence: 99%